The Impact Of Productive Zakat On The Economic Empowerment Program Based On Social Return On Investments (SROI): Case Study Of PT Karya Masyarakat Mandiri - Shofia Hidayat; Hendro Wibowo; Muhammad Doddy (Jurnal Ekonomi dan Perbankan Syariah, 2019)
Various programs are presented in zakat distribution practice. Productive zakat is one type of zakat that can provide sustainable benefits for the zakat mustahiq. PT KMM is a Social Enterprise formed by Dompet Dhuafa to focus on providing empowerment programs to the community as an effort to alleviate poverty. As an institution funded by zakat funds, PT KMM requires evidence on the impact and the extent of the impact of empowerment program that has been implemented for the sake of transparency of the distributed zakat funds. This study aims to calculate the impact produced by PT KMM using Social Return on Investment (SROI). The result of this study indicates that the SROI ratio was 4.89: 1. It means every Rp. 1 invested has generated benefit approximately Rp. 4.98 on economic, social and environment. This means that the empowerment program in the form of the Green Hortim M3 program through the Sumber Jaya Tani Community has the capability to yield benefits of 4.89 times greater than the input value invested.